Агенс та реципієнт у реченнях різного комунікативного спрямування - Даскалюк, Оксана Любомирівна (Чернівецький національний університет імені Юрія Федьковича, 2022)
The article describes the dependence of the roles of the agent and the recipient on the communicative purpose of the message
Keywords: agent, recipient, inducement, syntax and semantics of imperative subjects